2016
DOI: 10.1186/s13636-016-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acoustic similarity on efficiency of verbal information transmission via subtle prosodic cues

Abstract: In this study, we investigate the effect of tiny acoustic differences on the efficiency of prosodic information transmission. Study participants listened to textually ambiguous sentences, which could be understood with prosodic cues, such as syllable length and pause length. Sentences were uttered in voices similar to the participant's own voice and in voices dissimilar to their own voice. The participants then identified which of four pictures the speaker was referring to. Both the eye movement and response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…the Microsoft Windows chime) with deviants in sequences of the same sounds played backwards (Jacobsen et al, 2005). A self-voice advantage would also be consistent with results documenting facilitating effects of languageor speaker-familiarity on phonological and semantic processing (Chen et al, 2016;Fleming et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…the Microsoft Windows chime) with deviants in sequences of the same sounds played backwards (Jacobsen et al, 2005). A self-voice advantage would also be consistent with results documenting facilitating effects of languageor speaker-familiarity on phonological and semantic processing (Chen et al, 2016;Fleming et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…Vocal behavior is highly multidimensional and, either for anatomical or neural reasons, it is nearly impossible for speakers to produce for instance only the pitch aspects of a sad expression without simultaneously varying timbre or duration, or timbre aspects without simultaneously varying pitch (Figure 1 (Scherer et al 2001;Pell et al 2009), on familiar on nonfamiliar speakers (Chen et al 2016), male or female voices (Bonebright et al 1996), or even across speech and music (Juslin and Laukka 2003). When using emotional stimuli produced by actors, differences in decoding performance across groups may arise either because of production or perception differences.…”
Section: Specificitymentioning
confidence: 99%
“…consonant duration, omission of second syllable, etc. ), Pakarinen et al (2014) report MMN peak latencies ranging between 126–355 ms post stimulus-onset and Chen et al (2016) a peak MMNm of 265 ms; in contrast, with single-vowel stimuli involving more immediate timbre changes and no initial consonant, Carminati et al (2018) report MMN latencies ˜200 ms. Future work should better document the temporal profile of physical information available in the signal to discriminate deviants from standards, in order to more precisely determine the chronometry of their auditory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Right-lateralized temporal activations are in line with previous MMN studies that reported right activations for pitch deviants in tones and voice (Jiang et al , 2014, Lappe et al , 2016). In addition, the right anterior insula is involved in processing vocal emotions (Belin et al , 2004) and has also been associated with MMN responses to emotional syllable deviants (Chen et al , 2016).…”
Section: Discussionmentioning
confidence: 99%